IMPLEMENTASI CONVENTION ON INTERNATIONAL TRADE IN ENDANGERED SPECIES OF WILD FLORA AND FAUNA OLEH INDONESIA (KASUS PENANGANAN PERDAGANGAN ILEGAL TRENGGILING DI INDONESIA TAHUN 2005-2013) - Irjayani, Fitriyatul; Windiani, Reni; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Illegal trade animal species is a crime against referring to the action which is done inconflict with national laws and regulations. Indonesia is a country largest importersillegal trade Pangolin in Asia. Around the year 2000's Pangolin being one of the mostsought after to trade because the value of high economics, the biggest consumerdestination country in Asia are Cina and Vietnam. According to the data ministry ofthe forest in Indonesia specifically to ilegal trade Pangolin in one year can harm thestate about Rp. 8,23 billion. Hence for the handling of ilegal animal trade Indonesiaare working together to equal to CITES. This research aims to analyze the causes ofthe trade illegal Pangolin remained high in the period 2005-2013 although Indonesiaratified CITES since 1978. This research using the theory of international regimewith the paradigm neoliberalism to analyze the data collected through the literaturestudy, documentation, and interview. The result of research showed the cause of theCITES has not been successful is not because of a lack of interest, but the absence ofa good response in the face of the constraints that have been occurring.